2000
DOI: 10.1080/000164800750000216
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Adenosine 5'-ATP-induced Calcium Signaling in Isolated Vestibular Ganglion Cells of the Guinea Pig

Abstract: Extracellular adenosine 5'-triphosphate (ATP)-induced intracellular calcium concentration ([Ca2+]i) changes in acutely isolated vestibular ganglion cells (VGCs) of the guinea pig were investigated using the Ca2+ -sensitive dye Fura-2. Extracellular ATP induced an increase in [Ca2+]i in VGCs in a dose-dependent manner. ATP induced an increase in [Ca2+]i even in the absence of extracellular Ca2+ (1 mM Ethylene Glycol-bis (beta-aminoethyl Ether) N,N,N',N'-Tetraacetic Acid (EGTA)), thus suggesting that ATP induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In adult rat VGNs, immunohistochemistry demonstrated P2X 1 -P2X 6 subtypes as in SGNs [14]. [39]. Moreover, we recently characterized electrophysiological properties of ionotropic (P2X) conductance in VGNs (Table 4) [40].…”
Section: P2 Receptors In the Vestibular Partition (Vhc And Vgn)mentioning
confidence: 99%
“…In adult rat VGNs, immunohistochemistry demonstrated P2X 1 -P2X 6 subtypes as in SGNs [14]. [39]. Moreover, we recently characterized electrophysiological properties of ionotropic (P2X) conductance in VGNs (Table 4) [40].…”
Section: P2 Receptors In the Vestibular Partition (Vhc And Vgn)mentioning
confidence: 99%
“…Examples of the receptor demonstration course (P2XR in spiral ganglion neurons: SGNs, the counterpart of VGNs in the 8th cranial nerve) are: immunohistochemistry (Xiang et al, 1999), calcium responses (Cho et al, 1997), and then electrophysiology (Ito and Dulon, 2002;Salih et al, 2002). For VGNs, immunohistochemistry (Xiang et al, 1999) and calcium responses (Nagata et al, 2000) have already been reported. The present study achieved the next stage, electrophysiological proof of functional receptors.…”
Section: Contribution Of the Present Study To Research Into Purinergimentioning
confidence: 96%
“…P2X purinergic receptors on VGNs have already been detected immunohistochemically (Xiang et al, 1999) and by in situ hybridization (Kreindler et al, 2001). In terms of function, calcium signaling induced by ATP, with the possible involvement of P2X receptors, was shown (Nagata et al, 2000). However, the electrophysiological characteristics of P2X receptors, whether they can induce significant membrane currents in VGNs or not, have not been investigated.…”
Section: Introductionmentioning
confidence: 96%
“…The ATP-induced current was detected using patch-clamp experiments in the study, but the type of P2X receptor was not functionally identified. Another study also detected ionotropic and metabotropic P2 receptor activity in the adult guinea pig vestibular ganglion by performing intracellular [Ca 2+ ] imaging using Fura-2 AM but did not precisely identify the types of receptors [34]. A detailed discussion of the functional evidence and its implications for P2 receptors in the vestibular compartment will be described in the next sections.…”
Section: Distribution Of Purinergic Receptors In the Vestibular Systemmentioning
confidence: 99%
“…Two functional studies of P2 receptors have been reported to date. A study measuring intracellular [Ca 2+ ] using Fura-2 AM in the isolated adult guinea pig vestibular ganglion identified that ATP increased the [Ca 2+ ] in a dosedependent manner when administered in concentrations ranging from 0.1 to 1000 μM [34]. The increase in [Ca 2+ ] was even detectable without extracellular Ca 2+ , indicating that ATP induced Ca 2+ release from the intracellular stores, which was likely to be accomplished by P2Y receptors.…”
Section: Roles Of Purinergic Receptors In the Vestibular Ganglionmentioning
confidence: 99%